Interleukin 2 gene therapy of residual disease in mice carrying tumours induced by HPV 16 - Bubeník, J; Símová, J; Hájková, R; Sobota, V; Jandlová, T; Smahel, M; Sobotková, E; Vonka, V (International journal of oncology, 1999)
Experiments were designed to examine the efficacy of IL-2 gene therapy in a surgical minimal residual tumour disease, using moderately immunogenic MK16/1/IIIABC murine cells transformed by activated ras and HPV 16 E6/E7 oncogenes (MK16 cells). Previously we demonstrated that surgical minimal residual tumour disease (SMRTD) could be effectively cured when murine Mc12 sarcoma had been resected and the operated mice were treated with irradiated Mc12 sarcoma cells engineered to secrete IL-2. In this study we performed IL-2 gene therapy of MK16 carcinoma with two types of irradiated MK16-unrelated tumour cell vaccines. One type of vaccine was derived from MHC class I-matched Mc12 sarcoma cells engineered to secrete IL-2 and the other from MHC class I-discordant IL-2 producing plasmacytoma X63-m-IL-2. The vaccines did not share any tumour rejection antigen with the MK16 cells and served exclusively as a local source of IL-2 production. Both vaccines were capable of inhibiting MK16 tumours when administered peritumorally up to 15 days after MK16 tumour challenge. The irradiated MHC class I-matched and IL-2-producing Mc12 sarcoma vaccine was then selected for therapy of MK16 SMRTD. Whereas the recurrence rate in the operated MK16 carcinoma bearers was 80%, so that only 20% of mice were cured by surgery, approximately 65% of the MK16 carcinoma bearers were permanently protected when the surgery was followed by local administration of the IL-2-producing Mc12 sarcoma vaccine.
Keywords: Animals; Neoplasm, Residual; genetická terapie; interleukin-2; Papillomaviridae; Mice; transplantace nádorů; Interleukin-2; reziduální nádor; nádorové buňky kultivované; myši; Tumor Cells, Cultured; Male; Neoplasm Transplantation; Genetic Therapy; mužské pohlaví; zvířata; Mice, Inbred C57BL; myši inbrední C57BL